Deep Sequencing of the Human Retinae Reveals the Expression of Odorant Receptors - Jovancevic, Nikolina; Wunderlich, Kirsten A.; Haering, Claudia; Flegel, Caroline; Maßberg, Désirée; Weinrich, Markus; Weber, Lea; Tebbe, Lars; Kampik, Anselm; Gisselmann, Günter; Wolfrum, Uwe; Hatt, Hanns; et al. (Frontiers in Cellular Neuroscience, 2017)
Several studies have demonstrated that the expression of odorant receptors (ORs) occurs in various tissues. These findings have served as a basis for functional studies that demonstrate the potential of ORs as drug targets for a clinical application. To the best of our knowledge, this report describes the first evaluation of the mRNA expression of ORs and the localization of OR proteins in the human retina that set a stage for subsequent functional analyses. RNA-Sequencing datasets of three individual neural retinae were generated using Next-generation sequencing and were compared to previously published but reanalyzed datasets of the peripheral and the macular human retina and to reference tissues. The protein localization of several ORs was investigated by immunohistochemistry. The transcriptome analyses detected an average of 14 OR transcripts in the neural retina, of which OR6B3 is one of the most highly expressed ORs. Immunohistochemical stainings of retina sections localized OR2W3 to the photosensitive outer segment membranes of cones, whereas OR6B3 was found in various cell types. OR5P3 and OR10AD1 were detected at the base of the photoreceptor connecting cilium, and OR10AD1 was also localized to the nuclear envelope of all of the nuclei of the retina. The cell type-specific expression of the ORs in the retina suggests that there are unique biological functions for those receptors.